The Feynman chessboard model in 3 + 1 dimensions - Ord, G. N. (Frontiers in Physics, 2023)
The Chessboard model was Feynman's adaptation of his path-integral method to a two dimensional relativistic domain. It is shown that Chessboard paths encode information about contiguous pairs of paths in a spacetime plane, as required by discrete worldlines in Minkowski space. Applying the coding by pairs in a four dimensional spacetime is then restricted by the requirements of the Lorentz transformation, and implementation of these restrictions provides an extension of the model to 4-D, illuminating the relationship between relativity and quantum propagation.